Structural evidence for Nap1‐dependent H2A–H2B deposition and nucleosome assembly. (25th May 2016) - Aguilar‐Gurrieri, Carmen; Larabi, Amédé; Vinayachandran, Vinesh; Patel, Nisha A; Yen, Kuangyu; Reja, Rohit; Ebong, Ima‐O; Schoehn, Guy; Robinson, Carol V; Pugh, B Franklin; Panne, Daniel
Abstract: Nap1 is a histone chaperone involved in the nuclear import of H2A–H2B and nucleosome assembly. Here, we report the crystal structure of Nap1 bound to H2A–H2B together with in vitro and in vivo functional studies that elucidate the principles underlying Nap1‐mediated H2A–H2B chaperoning and nucleosome assembly. A Nap1 dimer provides an acidic binding surface and asymmetrically engages a single H2A–H2B heterodimer. Oligomerization of the Nap1–H2A–H2B complex results in burial of surfaces required for deposition of H2A–H2B into nucleosomes. Chromatin immunoprecipitation‐exonuclease (ChIP‐exo) analysis shows that Nap1 is required for H2A–H2B deposition across the genome. Mutants that interfere with Nap1 oligomerization exhibit severe nucleosome assembly defects showing that oligomerization is essential for the chaperone function. These findings establish the molecular basis for Nap1‐mediated H2A–H2B deposition and nucleosome assembly. Synopsis: A co‐crystal structure defines the stoichiometry of H2A–H2B binding to the Nap1 histone chaperone and shows that higher‐order oligomerization is needed for proper histone incorporation into nucleosomes. Crystal structure of the Nap1–H2A–H2B complex at 6.7 Å resolution. A Nap1 dimer binds a single H2A–H2B dimer. Nap1 prevents non‐specific DNA binding of H2A–H2B and is required for H2A–H2B deposition and nucleosome assembly in vivo . Oligomerization of the Nap1–H2A–H2B complex is important for the chaperone function of Nap1. Abstract : A co‐crystal structure defines the stoichiometry of H2A–H2B binding to the Nap1 histone chaperone, and shows that higher‐order oligomerization is needed for proper histone incorporation into nucleosomes.